2015
DOI: 10.3109/14767058.2015.1118039
|View full text |Cite
|
Sign up to set email alerts
|

Twin vaginal delivery is associated with lower umbilical arterial blood pH of the second twin and less intrapartum blood loss

Abstract: Twin vaginal deliveries were associated with slightly but significantly lower UmA-pH of the second twin, whereas twin cesarean delivery was associated with significantly larger intrapartum blood loss. Not only the neonatal risk but also the maternal risk should be taken into account when an optimal delivery mode for the twin pregnancy is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Our data showed that CS was significantly associated with postpartum haemorrhage. There were studies supporting our finding that mothers in the CS group were significantly more likely to have hemorrhage and surgical complications 23,29 , whereas other studies showed that mothers were more likely to suffer from haemorrhage with VD 30 . There were also studies with neutral findings showing no significant differences in postpartum haemorrhage rates between CS and VD 31,32 .…”
Section: Maternal Outcomes and Mode Of Deliverysupporting
confidence: 80%
See 1 more Smart Citation
“…Our data showed that CS was significantly associated with postpartum haemorrhage. There were studies supporting our finding that mothers in the CS group were significantly more likely to have hemorrhage and surgical complications 23,29 , whereas other studies showed that mothers were more likely to suffer from haemorrhage with VD 30 . There were also studies with neutral findings showing no significant differences in postpartum haemorrhage rates between CS and VD 31,32 .…”
Section: Maternal Outcomes and Mode Of Deliverysupporting
confidence: 80%
“…The retrospective cohort study in 2005 with 8073 twin births reported that CS reduced the risk of perinatal death of twins by approximately 75% 4 . Afterwards, several studies also reported that CS reduced perinatal and neonatal morbidities and mortalities [21][22][23] . However, the Twin Birth Study in 2013 with 1398 women between 32+0 to 38+6 weeks of gestation and twins in vertex presentation reported no significant differences between planned CS and planned VD in neonatal morbidities and mortalities 5 .…”
Section: Fetal Outcomes and Mode Of Deliverymentioning
confidence: 98%
“…Twin-to-twin delivery time interval was reported to be negatively correlated to the umbilical cord blood pH, and shorter DTI might improve the neonatal outcome for the second twins [22,23]. It was reported that DTI over thirty minutes was strongly associated with higher risks of fetal acidosis and low Apgar score in the second twin [24].…”
Section: Plos Onementioning
confidence: 99%
“…Additionally, in the second twins the percentage of umbilical arterial blood pH below 7.20 was significantly higher in VD than this in CS group (20% vs 4%; p = 0.0001). 8 Ylilehto et al showed that umbilical arterial blood pH < 7.05 appeared more often in VD second twins than in second CS twins (p = 0.003). 24 The team headed by Leung draws attention to the effect of delivery interval between twins and the duration of the 2 nd stage of labor.…”
Section: Discussionmentioning
confidence: 98%
“…6,7 Some authors reported that factors such as chorionicity, mode of delivery, type of fetal growth (discordant or symmetric), and birth mass worsen perinatal outcomes and increase the rate of neonatal complications in the second twin compared to the first one. [8][9][10] On the other hand, broad trials have been conducted which did not show the superiority of CS vs VD in terms of complications in neonates, especially in the absence of risk factors and when the first twin is in the cephalic presentation. [11][12][13] The authors of the meta-analysis from 2011, which included nearly 40,000 twin pairs, concluded that, in the absence of risk factors, VD is safer than CS for the first twin but for the second twin, the mode of delivery had no effect on perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%